Source apportionment of processes contributing to volcanic PM10 aerosols during the 2021 eruption of Tajogaite - Jessica López-Darias; Sergio Rodríguez; Jesús de la Rosa; Jon Vilches; Thomas Boulesteix; Noémie Taquet; Ibtissem Belbachir; Gorka Villena-Armas; Ana M. Sánchez de La Campa; Omaira García; Juan H. Ayala (Science of The Total Environment, 2025)

The evolution of amino acids under asteroidal aqueous alteration - Y.Y. He; S. Bernard; M. Lecasble; J.-C. Viennet; I. Criouet; D. Boulesteix; N. Khodorova; L. Delbes; M. Guillaumet; F. Baudin; B. Laurent; A. Buch; et al. (Geochimica et Cosmochimica Acta, 2024)

Influence of pH and salts on DMF-DMA derivatization for future Space Applications - D. Boulesteix; A. Buch; J. Samson; M. Millan; J. Jomaa; D. Coscia; V. Moulay; O. McIntosh; C. Freissinet; J.C. Stern; C. Szopa (Analytica Chimica Acta, 2023)

Insertion polymorphism of transposable elements and population structure of Anopheles gambiae M and S molecular forms in Cameroon - M. BOULESTEIX; F. SIMARD; C. ANTONIO‐NKONDJIO; H. P. AWONO‐AMBENE; D. FONTENILLE; C. BIÉMONT (Molecular Ecology, 2007)
The insertion polymorphism of five transposable element (TE) families was studied by Southern blots in several populations of the M and S molecular forms of the mosquito Anopheles gambiae sensu stricto from southern Cameroon. We showed that the mean TE insertion site number and the within‐population insertion site polymorphism globally differed between the M and S molecular forms. The comparison of the TE insertion profiles of the populations revealed a significant differentiation between these two molecular forms (0.163 ST